Work and Television - Giacomo Corneo (Institute for the Study of Labor (IZA), 2001)
Evidence from a sample of countries show that people roughly spend as much time watching television as earning their living. Moreover, television viewing and work hours are positively correlated across countries. A simple model based on complementarities in the organization of free time is developed that explains such a pattern as resulting from multiple equilibria. In this model the equilibria can be inversely Pareto-ranked by their amount of television viewing. Arguments are offered to explain why in some countries a Pareto-inferior equilibrium might have come into being.
Keywords: J2; H0; D1; 330; Television viewing; work hours; relational goods; Fernsehen; Arbeitszeit; Zeitallokation; Konsumtheorie; Freizeitökonomik; Soziales Verhalten; Theorie; Welt